Sphenoidal pneumosinus dilatans associated compressive optic neuropathy: A case series of four adolescent patients - Xuejun Zhou; Quangang Xu; Buhuan Zhang; Yongzhe Liu; Xinying Liu; Songfeng Wang; ShiMing Yang; Xiaolu Wang (Heliyon, 2024)
Visual impairment caused by pneumosinus dilatans (PSD) among adolescents is a rare condition, which is associated with a high blinding rate due to the lack of clinical manifestations and effective treatment. The use of magnetic resonance imaging (MRI) and computed tomography (CT) may be helpful in diagnosis of PSD, and the endoscopic transnasal optic nerve decompression (ETOND) can improve the vision of PSD patients with visual impairments. This case series report detailing the diagnosis and treatment of visual impairments caused by PSD has improved clinicians’ understanding of this disease and helped reduce misdiagnoses and missed diagnoses. This article also highlighted the efficacy of this less invasive technique in managing optic nerve compression caused by sphenoidal pneumosinus dilatans (SPSD) in pediatric patients. In addition, this report proposed a novel aspect to explore the etiology of PSD and suggested the significance of proper terminology use when describing different PSD conditions, as well as possible future mechanisms explorations.